Composting of Night Soil and Horse Manure with Leaves as Organic Substrate. Issue 3 (1st October 2020) - Zhang, Hong-xia; Sun, Xiao-jie; Shan, Hui-jun; Xue, Chen-nan; Wang, Jia-jie
Abstract: This study aims to investigate the characteristics of night soil/horse manure with leaf co-composting using aerobic static composting method. Two influencing factors, including composting materials and aeration pattern, were investigated by determining the change in the principal physicochemical properties, i.e. temperature, volatile solid, carbon, nitrogen, hydrogen, carbon-to-nitrogen ratio, heavy metals, ammonia nitrogen, nitrate nitrogen, and germination index (GI). The mixture of horse manure and leaf can achieve high composting temperature, long retention time of high temperature (55 °C), fast organic matter degradation, and high GI under the same aeration pattern. Under the same composting materials, the intermittent aeration pattern during composting was superior to the continuous aeration pattern because the former promoted the composting process.